Petrogenesis of Primitive Lavas from the Toro Ankole and Virunga Volcanic Provinces: Metasomatic Mineralogy beneath East Africa's Western Rift - Pitcavage, Erica; Furman, Tanya; Nelson, Wendy R.; Kalegga, Peggy K.; Barifaijo, Erasmus (Lithos, 2021)
Geochemical analysis of magmas erupted in continental rifts are a valuable tool for understanding the compositional, physical, and thermal controls on rift related magmatism. Bulk rock geochemistry and geochronology of lavas from volcanic fields in the Western Rift of the East African Rift System provide insight into the sources and processes of petrogenesis of magmas in the region, as well as insight into the spatial variability of metasomatic history of the lithospheric mantle. Lava compositions from three primitive volcanic fields in southwestern Uganda (Bufumbira, Virunga Volcanic Province; Katwe-Kikorongo and Bunyaruguru, Toro Ankole Volcanic Province) are potassic (K2O/Na2O = 0.3–2.7) and enriched in incompatible trace elements (e.g., (La/Yb)n = 12–132); the Toro Ankole samples are also silica-undersaturated. The compositions of these lavas require significant input from metasomatized sub-continental lithospheric mantle (SCLM), likely consisting of a pyroxenite containing variable amounts of garnet, amphibole, phlogopite, and accessory minerals including titanite, apatite, and zircon, produced through infiltration by spatially varying carbonatitic and silicate metasomatic agents. A subset of lavas record 40Ar/39Ar ages = 21–662 ka, with minor geographic and compositional trends apparent in the temporal development of the volcanic fields.
Keywords: East african rift; Metasomatism; Alkaline volcanism; Lithospheric melting